Global Trends in Genre-Based Approach Research in Language Learning: Bibliometric Analysis (2015–2025) - Rosdiana, Rina; Boeriswati, Endry; Murtadho, Fathiaty (Proceeding International Conference on Education, 2025)
Bibliometric analysis maps the genre-based approach (GBA) as part of efforts to support education for Sustainable Development in the last ten years. The Scopus database was used to analyze 169 documents out of 260 documents on the topic of GBA. Data was obtained from 2015-2025*. With restrictions on the subject area of social science, which has been published in Scopus, and in English. The important finding is that this research has generally increased in the number of publications although in some years there has been a decrease, but the decrease is slight.  The article in this bibliometric study discusses the topic of GBA, most of which has been published in journals by international journals indexed by Scopus with quartile 1. In addition, the authors with the most citations come from articles published in Q1. The United States is the most productive country in conducting research on this topic of GBA. Indonesia is in second place, and in third place is Australia, the initiator of this approach in language learning. Universities in Indonesia are represented by the Indonesia University of Education in the top ten that published this research. In its discussion, this study uses Vosviewer. Thirteen clusters were found. Eight of them have a lot of connections to other topics: GBA has given rise to research related to writing learning, sfl, esp, academic writing, efl leaners.  Several other important findings were also obtained that can be used to conduct further research.